Gastric Mucosa Mucous Layer Thickness in Liver Cirrhosis with Portal Hypertensive Gastropathy Compare to Functional Dyspepsia - Loli J Simanjuntak; Chudahman Manan; Marcellus Simandibrata; Vera Yuwono; Rino Alvani Gani; Sabarinah Prasetyo (The Indonesian Society for Digestive Endoscopy, 2004)
Background: This study aimed to investigate gastric mucosa mucous layer thickness in portal hypertensive gastropathy (PHG) compare to normal mucosa in functional dyspepsia and its correlation with several variables such as child class, severity of esophageal varices and gastropathy. Methods: Biopsy specimens were taken from the antrum and corpus from both group of patients with PHG and functional dyspepsia. The specimen was given cryometric for frozen section. Tissue were sliced by sagital section 11 µm, placed in object glass, fixed and stained to evaluate mucous thickness and giemsa stained to observe Helicobacter pylori. Measurement of mucous thickness was done upward muscularis mucosa started from upper epithelial layer from foveale tip until outer mucous layer on 15 points which were marked randomly and calculate the mean value by micrometer (µm). Results: Mean value of antral mucous thickness in PHG was 13.30 ± 6.5 µm, while in the functional dyspepsia it was 25.59 ± 5.66 µm. Statistical analysis for both kinds of mucous thickness was p0.001. Mean corpus mucous thickness in PHG was 10.6 ± 6.81 µm, while mucous thickness in dyspepsia was 32.54 ± 6.51 µm. Statistical analysis revealed p0.001. This result showed significant difference of mucous thickness of antrum and corpus statistically between PHG and dyspepsia as control group. Conclusion: The study had proven the presence of decreased gastric mucosa mucous layer thickness in corpus and antrum in PHG. Thus, therapeutic approach to increase mucous thickness must be considered in patients with PHG. Keywords: Gastric mucosa, PHG, liver cirrhosisemistry